(untitled) (Jurnal Ilmiah Pertanian Nasional, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector in agricultural product processing, such as banana sale (traditional smoked/fried bananas), possesses significant market potential but is often hindered by strategic gaps between internal operational capacities and external opportunities. This study aims to quantitatively measure the strategic position of the "Kembang Wijaya" Banana Sale MSME in Kediri City and formulate an optimal development strategy by integrating operational and marketing aspects. The research method employed is a descriptive-analytical approach with a single case study. Primary data were collected through in-depth interviews with the business owner and production staff to validate triangulation. Data analysis was conducted using the Internal Factor Evaluation (IFE) Matrix and the External Factor Evaluation (EFE) Matrix. The results showed a total IFE score of 2.35, indicating an internal position below the average (moderate to weak) due to reliance on manual production processes and short product shelf life. Meanwhile, the total EFE score of 2.85 indicates a good response to conducive external opportunities. Based on these coordinate positions, the recommended strategy is selective growth. This strategy focuses on leveraging business legalities (P-IRT and SIUP) to expand into digital markets (online marketplaces), while balancing investment in appropriate technology, such as spinner machines, to increase production efficiency and extend product shelf life to support wide-range distribution. Sektor Usaha Mikro, Kecil, dan Menengah (UMKM) pengolahan produk pertanian seperti sale pisang memiliki potensi pasar yang besar, namun sering kali terhambat oleh kesenjangan antara kapasitas operasional internal dan peluang eksternal. Penelitian ini bertujuan untuk mengukur posisi strategis UMKM Kripik Sale Pisang "Kembang Wijaya" di Kota Kediri secara kuantitatif dan merumuskan strategi pengembangan yang optimal melalui integrasi aspek operasional dan pemasaran. Metode penelitian yang digunakan adalah deskriptif-analitis dengan pendekatan studi kasus tunggal. Data primer dikumpulkan melalui wawancara mendalam dengan pemilik usaha dan karyawan produksi untuk validasi triangulasi. Analisis data dilakukan menggunakan Matriks Evaluasi Faktor Internal (IFE) dan Matriks Evaluasi Faktor Eksternal (EFE). Hasil penelitian menunjukkan total skor IFE sebesar 2,35, yang mengindikasikan posisi internal berada di bawah rata-rata (sedang menuju lemah) akibat ketergantungan pada proses produksi manual dan masa simpan produk yang singkat. Sementara itu, total skor EFE sebesar 2,85 menunjukkan respons yang baik terhadap peluang eksternal yang kondusif. Berdasarkan posisi koordinat tersebut, strategi yang direkomendasikan adalah strategi pertumbuhan selektif. Strategi ini difokuskan pada pemanfaatan legalitas usaha (P-IRT dan SIUP) untuk ekspansi ke pasar digital (online marketplace), yang wajib diimbangi dengan investasi teknologi tepat guna seperti mesin spinner untuk meningkatkan efisiensi produksi dan memperpanjang masa simpan produk guna mendukung distribusi jangkauan luas.